2017
DOI: 10.3892/mmr.2017.7078
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shu Gan Jian Pi formula on rats with carbon tetrachloride-induced liver fibrosis using serum metabonomics based on gas chromatography-time of flight mass spectrometry

Abstract: Liver fibrosis is a common stage in the majority of chronic liver diseases, regardless of the etiology, and its progression may lead to hepatic cirrhosis or hepatocellular carcinoma. Metabolomics, a powerful approach in systems biology, is a discipline used to qualitatively and quantitatively analyze the small molecule metabolites of cells at specific times and under certain conditions. The present study aimed to investigate serum metabolic changes following Shu Gan Jian Pi formula (SGJPF) treatment of carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Liver fibrosis is a complex pathological process that leads to the development of chronic liver disease and cirrhosis 26,27. Liver cirrhosis not only leads to hepatic functional failure but also causes a series of complications 28.…”
Section: Discussionmentioning
confidence: 99%
“…Liver fibrosis is a complex pathological process that leads to the development of chronic liver disease and cirrhosis 26,27. Liver cirrhosis not only leads to hepatic functional failure but also causes a series of complications 28.…”
Section: Discussionmentioning
confidence: 99%
“…There are lots of ways to build experimental liver injury animal models, among which CCL 4 is widely selected to induce liver injury (Clichici et al, 2015; Endig et al, 2019). In recent years, because of the advantages Chinese herbal medicines offer in treating liver injury, such as better efficacy and fewer side effects, many relevant studies have been initiated (Jiang, Qin, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, KEGG analysis revealed that the DE genes were mainly enriched in the metabolic process, which were closely related to previous studies. For example, our previous studies indicated that dysregulations of cytochrome P450, sphingolipid, glucose and water electrolyte, fatty acid, amino acid and energy metabolism might be involved in the pathogenesis of HF in rats [32,33].…”
Section: Discussionmentioning
confidence: 99%